Steam plant calculations manual - Ganapathy, V., 1923- (Mechanical engineering (Marcel Dekker, Inc.) ;, 1994)
"Maintaining a question-and-answer format, this second edition provides simplified means of solving nearly 200 practical problems that confront engineers involved in the planning, design, operation and maintenance of steam plant systems. Calculations pertaining to emissions, boiler efficiency, circulation and heat transfer equipment design and performance are provided. Solutions to 70 new problems are featured in this edition.Maintaining a question-and-answer format, this second edition provides simplified means of solving nearly 200 practical problems that confront engineers involved in the planning, design, operation and maintenance of steam plant systems. Calculations pertaining to emissions, boiler efficiency, circulation and heat transfer equipment design and performance are provided."--PUBLISHER'S WEBSITE.